Removal of Acid Brown 354 from wastewater by aminized cellulose acetate nanofibers experimental and theoretical study of the effect of different parameters on adsorption efficiency - Namjoufar, Mehran (Water science and technology : a journal of the International Association on Water Pollution Research, 2021)
Wastewater effluents usually involve dyes that are dangerous for aquatic life and other environments. Many of these dyes are toxic, carcinogenic, and can cause skin and eye irritation. In this study, firstly aminized cellulose acetate was prepared from cellulose acetate and applied for the adsorption of Acid Brown 354 from aqueous solutions. The effects of different parameters including adsorbent dosage, pH, temperature, and initial concentration of dye on adsorption capacity were examined. Results showed that removal efficiency of dye declined by increasing values of all parameters. Finally, maximum removal of dye was achieved in the presence of 0.1 g adsorbent, pH of 2, and 10 mg/L of initial dye concentration at a temperature of 25 °C. Also, different adsorption isotherms were investigated including Langmuir, Temkin, and Freundlich models and results demonstrated that the adsorption isotherm of dye followed the Freundlich model with a correlation coefficient of 0.988 revealing that the bond between the dye and the adsorbent is strong. Finally, kinetic study indicated that the adsorption of dye is exactly governed by pseudo-second-order kinetics explaining that the adsorption process is chemical and the adsorbent can not be reused